(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Farmers in India face risk and uncertainty on a regular basis due to susceptibility of agriculture to various risks arising from weather variability, fluctuation in the input and output prices, difficulties in storage, pest attack and plant diseases etc. Traditional measures of risk mitigation such as self- insurance, borrowings, crop diversification cannot work effectively in catering to catastrophic shocks. One important policy intervention to reduce production and market risks is to provide crop insurance in the event of adverse situation. Crop insurance is a potential market-based intervention that helps farmers to cope with systematic shocks and stabilise their income. But providing insurance against a crop failure is not as easy as that of against accidents, fire etc. The covariate nature of agricultural risk goes against the working of insurance market and makes government funding imperative for crop insurance to be available for farmers. Apart from this, there is a substantial amount of asymmetric information that restricts private participation in crop insurance business. Research on working and dynamics of crop insurance is fairly recent. The present paper reviews and discusses the recent developments in the literature on crop insurance. The paper reports the empirical study on the impact of crop insurance on output, input use and willingness to pay for insurance.